Politik Hukum Dalam Pembentukan Peraturan Perundang-Undangan Nasional - Maharani, Ananda Dewi; Huda, Uu Nurul (Sharia Journal and Education Center Publishing, 2025)
Law formation is a state function carried out by the executive, legislative and judicial bodies to form laws, both written and unwritten. By using the method of analysis, exploration, explanation, and exposure. In this context, it is important to design a scenario of national legislation politics that is oriented towards understanding the concept of a national legal system. The goal is to realize a state of law that is just, democratic, and based on justice and truth that serves the interests of the people and the nation. In addition, the formation of law is also influenced by the political configuration behind it, where law acts as a means of dominant political power. Thus, an understanding of legal politics and its relationship with legal formation is very important in the context of responsive and equitable legal development.